Mexico : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2012)
This paper discusses the Financial System Stability Assessment of Mexico. The Mexican banking system is profitable, liquid, well capitalized, and stress tests suggest that it is able to withstand severe shocks. The strength of capital buffers has persuaded the authorities to introduce Basel III capital requirements in 2012, well ahead of other countries. The institutional set-up for macrofinancial oversight and systemic crisis management has been strengthened with the establishment of the Financial System Stability Council.